2015
DOI: 10.1161/circulationaha.114.014992
|View full text |Cite
|
Sign up to set email alerts
|

Association of Discharge Aspirin Dose With Outcomes After Acute Myocardial Infarction

Abstract: Background-Aspirin is the most widely used antiplatelet drug postmyocardial infarction, yet its optimal maintenance dose after percutaneous coronary intervention with stenting remains uncertain. Methods and Results-We compared outcomes of 10 213 patients with myocardial infarction who underwent percutaneous coronary intervention and were discharged on dual-antiplatelet therapy at 228 US hospitals in the Treatment with ADP Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events after Acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…This study had some characteristics that might have affected the bleeding rate as follows: (1) there was a high proportion of patients with TRA-PCI in the present study (91.20%); (2) a low percentage of the population received oral triple therapy comprising anticoagulants, aspirin, and a P2Y12 receptor inhibitor ( n = 17, 0.17%); (3) none of the maintenance doses of aspirin were higher than 100 mg; and (4) there was a low rate of using ticagrelor in 2013 in China (only 0.13% in this study). Previous studies showed that the use of the TRA[ 11 ] and a low maintenance dose of aspirin may decrease the incidence of bleeding,[ 14 15 16 ] triple therapy,[ 17 18 ] and the use of strong P2Y12 receptor inhibitors may increase the bleeding risk. [ 19 ] All of the above factors might affect the PARIS bleeding score's predictive value in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study had some characteristics that might have affected the bleeding rate as follows: (1) there was a high proportion of patients with TRA-PCI in the present study (91.20%); (2) a low percentage of the population received oral triple therapy comprising anticoagulants, aspirin, and a P2Y12 receptor inhibitor ( n = 17, 0.17%); (3) none of the maintenance doses of aspirin were higher than 100 mg; and (4) there was a low rate of using ticagrelor in 2013 in China (only 0.13% in this study). Previous studies showed that the use of the TRA[ 11 ] and a low maintenance dose of aspirin may decrease the incidence of bleeding,[ 14 15 16 ] triple therapy,[ 17 18 ] and the use of strong P2Y12 receptor inhibitors may increase the bleeding risk. [ 19 ] All of the above factors might affect the PARIS bleeding score's predictive value in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4 After the initial loading dose, subsequent administration of low-dose aspirin (ie, 81 mg daily) is associated with lower gastrointestinal bleeding with the same cardiovascular benefit as higher daily doses. 5,6 Per the 2013 ACC/AHA STEMI guidelines, after an initial aspirin loading dose of 162 to 325 mg, a daily dose of 81 mg is often continued indefinitely for secondary prevention. 7 Likewise, the 2017 ESC STEMI guidelines recommend aspirin administration for all patients without contraindications (class I recommendation).…”
Section: Maintaining Myocardial Perfusion During St-segment Elevationmentioning
confidence: 99%
“…While there is strong evidence to support aspirin treatment for the secondary prevention of ASCVD in contemporary practice guidelines, registries and post hoc analyses from randomized clinical trials have shown discordant results with respect to aspirin dosage on ischemic events in the post-ACS setting . Moreover, variable use of aspirin in low or high dosages for post-ACS treatment in clinical practice exists, reflecting the uncertainty among clinicians regarding the optimal dosage for long-term secondary prevention.…”
Section: Introductionmentioning
confidence: 99%